Bezpieczeństwo społeczności lokalnych a mit bezpiecznego państwa jako zjawiska kulturowe .......... 105 - Szczurowski, Maciej (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
Two security models have developed in Poland, one of which has a national dimension and the other a local one. This is the result of a phenomenon known as culture created at various levels of social structures. The main goal of local communities is to achieve social security. Next, we show activity to ensure our safety in the local space in the form of schools, nurseries, good, well-lit roads, public order etc. At the local level we shape the actual state of our safety. The differences in the understanding of security in the state and local dimension are primarily due to the fact that the political basis of the functioning of the state is the political myth. Hence, our political mythology is colorful and diverse. The nineteenth and twentieth centuries clearly showed that Poland is not coping with creating a safe state for the nation. Security is guaranteed by pragmatism, which, for a cure, but political mythology is doing great. Therefore, it is time to modify the model of the state and amend the national mythology, closely related to the symbol of the homeland, for which we will not only give our lives, but which, following the example of local communities, will above all become our home, where we will feel safe and live in mutual respect.